Case Report: Modified Taulinoplasty: a new technique for minimally invasive repair of pectus excavatum - Frediani, Simone; Beati, Federico; Pardi, Valerio; Aloi, Ivan Pietro; Bertocchini, Arianna; Accinni, Antonella; Reali, Simone; Schingo, Paolo Maria Salvatore; Inserra, Alessandro (Frontiers in Surgery, 2024)
Introduction: About 95% of congenital chest wall deformities are pectus abnormalities, with pectus excavatum (PE) being the most common. The purpose of this work is to offer a modified Taulinoplasty Technique based on 35 consecutive PE patients' one-year single-center experience in 2022. Technique: One minimally invasive procedure for PE is taulinoplasty. In order to prevent invasion of the mediastinum or pleural cavity, it is considered that external traction can be used to raise the sternum. Our experience indicates that the most common surgical consequences of this procedure—which involves creating a submuscular and subcutaneous tunnel to install the metal device—are post-operative seroma and wound dehiscence. We modified the conventional method to achieve more aesthetically pleasing results. Discussion: Taulinoplasty seems to be a safe technique, easier and more feasible than standard Taulinoplasty, with better outcomes in terms of surgical complications, although further experience is necessary to confirm our preliminary data.